The Analysis of Capacity Increase in Beef Cattle Population in The South Konawe Regency - Musram Abadi; La Ode Nafiu; La Ode Arsad Sani (Buletin Peternakan, 2021)
This research aimed to determine the maximum potential for increasing the population of beef cattle in the South Konawe Regency Southeast Sulawesi Province based on natural resources and the ability of the head of the farmer family to raise cattle. This research was conducted 5th October to 28th December 2019. Determination of research location was carried out purposely (purposive sampling), with the consideration that South Konawe Regency was a central area for Bali cattle breeding.  The data analysis was carried out by analyzing the supporting capacity of forage from pasture land and non-pasture land (rice fields, plantations, forests and moor) as well as the production of agricultural food crop waste (rice, corn, peanuts, green beans, cassava, sweet potatoes and soybeans), using tabular data in the form of data on food crop production and land area. Potential analysis of beef cattle business development in South Konawe Regency using the calculation of the Capacity Increase of Ruminant Population/Kapasitas Peningkatan Populasi Ternak Ruminansia (KPPTR). Based on the results of research in South Konawe Regency, the number can still be increased by 7,478 Animal Units. If the value is converted to adult female-male cows with an age of >2 years, the population addition can be done as many as 7,478 cows. Meanwhile, if converted to female-male heifers with an age of 1-2 years, the population increase can be increased by 14,956 and if converted to female-male calves with an age of >1 year, the population increase can be done up to 28,912.